Infection Control Measures among Dental Professionals, Interns, and Students in Prosthodontic Department - Dixit, S; Dixit, P B; Pradhan, D; Gupta, S (Journal of Nepalese Prosthodontic Society, 2020)
Introduction: Dental professionals frequently encounter infectious agents. Those not practicing proper infection control measures are at serious risk of infections. This study was conducted to assess knowledge, attitude, practice, and satisfaction of dental professionals regarding infection control guidelines to be followed in Prosthodontics. Materials and Methods: This cross-sectional descriptive study was conducted from August to October 2020 in department of Prosthodontics, Kathmandu Medical College after obtaining ethical clearance and informed consent. Participants comprised of dental surgeons, interns, students, and faculties who were recruited by convenience sampling. The data on the questionnaire were collected via Google forms and analysed with Microsoft Excel. Descriptive statistics have been presented as frequency and percentages. Results: A total of 154 questionnaires filled by 39 (25.32%) males and 115 (74.68%) females of mean age of 25.02±4.85 years were analysed. Of all, 25 (16.23%) had never had a lecture and 118 (76.62%) had never had attended clinical demonstration or hands-on workshop on infection control. Only 129 (83.77%) had received immunisation for hepatitis B. Most (144, 93.51%) preferred mouth rinse before any procedure; 145 (94.16%) agreed that disinfection is required between patients; and only 77 (50%) of the participants washed their hands prior to wearing gloves. Majority (123, 79.97%) were not satisfied with their knowledge and performance. Conclusions: Knowledge and attitude of participants regarding infection control was found adequate and positive, though lacking in practice. It is recommended that the infection control lectures and clinical demonstrations be increased in curriculum so that no future dentists are deprived of essential knowledge.